Penerapan Game Edukasi Word Wall untuk Meningkatkan Penguasaan Kosakata Bahasa Arab - Sriwulan, Sriwulan; Kartini; Said, Rukman AR.; Hasnidar (Pedagogical Education and Review of Linguistics, 2026)
This study discusses how the application of word wall educational games to improve the mastery of Arabic vocabulary of class VIII students at the palopo city state tsanawiyyah madrasah. This research used pre-experimental method with one group pre-test and post-test design. Data collection was done through observation, test, and documentation. The research instruments were tested using validity and reliability tests to ensure the feasibility of the data. Data were analyzed using normality test, Wilcoxon test, and N-Gain test. The results showed a significant increase in students' mastery of Arabic vocabulary after the application of Word Wall. The mean score increased from 46 in the pre-test to 61.33 in the post-test. Wilcoxon test resulted in Asymp. Sig. (2-tailed) value of 0.003 <0.05, which indicates a significant difference between the pre-test and post-test scores. Based on the N-Gain test, the effectiveness of the Word Wall application was in the medium category with a score of 0.35 (35.46%). The application of Word Wall proved to be effective as a fun and innovative learning alternative to improve students' vocabulary mastery.